Analisis Stabilitas Fisik dan Kimia Sediaan Sirup Parasetamol di Suhu Penyimpanan Berbeda (Penelitian laboratorium untuk menilai kestabilan sediaan farmasi berdasarkan kondisi penyimpanan) - Mukriani, Mukriani; Rahmat, Rezqiqah Aulia (Barongko: Jurnal Ilmu Kesehatan, 2025)
Background: Paracetamol is a widely used antipyretic and analgesic drug, particularly in syrup form for children. The stability of syrup preparations is significantly influenced by storage conditions, particularly temperature. Objective: This study aimed to analyze the physical and chemical stability of paracetamol syrup preparations stored at different temperatures. Methods: An experimental laboratory study was conducted on three storage groups: room temperature (25±2°C), cold temperature (4±2°C), and high temperature (40±2°C) for 30 days. Physical stability evaluation included color, clarity, pH, and viscosity, while chemical analysis was performed using UV-Vis spectrophotometry to measure paracetamol levels. Results: The results showed that syrup stored at high temperatures experienced a significant decrease in active ingredient levels (up to 20%) and changes in pH. Preparations stored at cold and room temperature remained physically and chemically stable throughout the test period. Conclusion: High storage temperatures accelerate the degradation of paracetamol in syrup preparations, so it is recommended to store at room temperature or refrigerated to maintain stability.